Renewable Energy Strategies to Overcome Power Shortage in Kurdistan Region of Iraq - Al-Din, Salar Salah Muhy; Kuzovic, Dusko R; Iranfar, Maryam (Industrija, 2017)
The aim of this paper is to investigate the possibility of applying renewable energy strategies in Kurdistan Region of Iraq to overcome the shortage of electricity supply. Finding alternative renewable sources could overcome the problem. The renewable energy will reduce CO2 emission in the cities which considers the main source of pollution. That will participate in reducing the effect of global warming. The study tries to investigate the direct solar renewable energy through two of the main renewable energy categories to produce electricity based on a survey of literature review. Photovoltaic and wind power technologies are possible to be conducted in the region to overcome power shortage.
Keywords: Energy; Kurdistan Region of Iraq; Solar Radiation; Renewable energy